Electrochemical characterization of laser‐carbonized polyacrylonitrile nanofiber nonwovens. Issue 25 (9th March 2018) - Go, Dennis; Opitz, Martin; Lott, Philipp; Rahimi, Khosrow; Stollenwerk, Jochen; Thomas, Helga; Möller, Martin; Roling, Bernhard; Kuehne, Alexander J. C.
ABSTRACT: Porous carbon materials represent prospective materials for absorbers, filters, and electronic applications. Carbon fibers with high surface areas can be produced from polyacrylonitrile and spun as thin fibers from solution. The resulting polymer fibers are first stabilized to obtain conjugated ribbons and then carbonized to graphitic structures in a second high‐temperature step in an inert atmosphere. In this study, we investigated a previously described fast laser‐heating process that delivered fibers with a higher crystallinity and surface area compared to the thermally carbonized fibers. In a subsequent KOH‐activation step, the crystalline domains were exfoliated, and the surface of the fibers became macroporous. This led to a reduced specific surface area but a higher capacitance compared to thermally carbonized nanofibers. We report the electrochemical properties of the electrochemical cells and discuss their potential applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46398. Abstract :